Leaching of Picloram in ultisol under different rainfall volumes - Assis,E.C (2011)
The present study aimed to evaluate the leaching potential of Picloram in Ultisol columns under different rainfall amounts. For such, 30 treatments were evaluated (one soil associated with three levels of rainfall and ten depths).The experiments were arranged in a split-plot design, in a completely randomized design, with four replications. PVC columns of 10 cm in diameter and 50 cm in length were filled with these soils, moistened, and placed upright for 48 hours to drain the excess water. The herbicide was applied and rainfall simulations were carried out at specified intensities, according to the treatments, to force Picloram leaching. After 72 hours, all the columns were arranged in a horizontal position and opened lengthwise. Then, soil sampling was carried out every 5 cm of depth for subsequent herbicide extraction and quantification and analysis by high performance liquid chromatography. The remaining soil samples were placed in plastic pots, and, at the respective depths, the indicator species Cucumis sativus was sown. Twenty-one days after the emergence (DAE) of the indicator plants, evaluations were conducted to verify the symptoms of toxicity caused by Picloram in the plants. It was concluded that Picloram leaching is directly dependent on the volume of rain applied. The herbicide reached the deepest regions in the soil with the highest intensity of rain. The results obtained by bioassay were in agreement with those found by liquid chromatography.